Fungsi Peristiwa pada Gastronomi Sastra dalam Dongeng Putri Lyla yang Sombong Karya Dyah Umi Purnama - Permatasari, Annisa; Suyatno, Suyatno; Indarti, Titik (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2023)
Fairy tales are a means of assistance so messages can be conveyed to children. Indonesia is highlighting stunting. Stunting can be prevented if children and their parents are aware of the importance of nutritious food. Apart from being a basic need for human life, food is also a cultural construction and philosophy of life. Food should have a story about insight or background and goals, one of which is nutrition. The function of events in literary gastronomy in fairy tales is to provide information regarding the actions and events of a story. The presence of an event perspective in literary gastronomy provides an alternative understanding of stories. This study uses a literary gastronomic function research methodology. The source of the data in this study is the fairy tale Princess Lyla the Arrogant by Dyah Umi Purnama which was published in 2019. The data collection technique in this study used the read-note technique. Data analysis techniques are in the form of organizing and sorting data into patterns, categories, and basic descriptive units. Based on these events, it is found that the PLS story has an advanced plot. The main event in the tale is Princess Ghidzai who shows that eating tempeh does not make one stupid. While the supporting events are in the form of opposition from Princess Lyla to tempeh to the queens who provide expensive food. The function of this fairy tale event is to explain the concept of the events and actions of the characters in the fairy tale so that it can motivate readers (children and/or children's guardians) to be more respectful of food, find out food nutrition, and be creative with food